The essence of the state-legal function of the Prosecutor in the criminal process of the Kyrgyz Republic (Journal of actual problems of jurisprudence, 2019)
The author carried out the analysis of the procedural status and function of bodies of supervision in modern criminal legalproceedings of the Kyrgyz Republic, in particular public prosecutor’s supervision of legality in criminal procedure activity of theinvestigation authorities, promoting providing guarantees of legality at investigation of crimesКеуwords: attorney, criminal procedure, the functions of the state, a consequence of the law.